Hybridity and Paradox: The Cultural Bridge of Gen Z (A Critical Multimodal Discourse Analysis on the X Account @Aniesbubble) - Ondo Ria (Green Publisher Indonesia, 2024)
Social media, such as Twitter, enable immediate and delayed interaction with a wide audience. Online personas of political figures, such as the X account @aniesbubble, are in the spotlight in the 2024 election campaign, especially in attracting the attention of potential young voters in Indonesia. This research aims to ana-lyze the critical multimodal discourse on X @aniesbubble account in the context of the 2024 election political campaign. The main focus is to understand how multimodal ele-ments are used to shape opinions and interactions with audiences, as well as the implica-tions of using this strategy in cultural and political contexts. This research uses a qualita-tive method with a multimodal critical discourse analysis approach. The main data was taken from the X @aniesbubble account in the time period before the general election until the determination of the election winner. The analysis was conducted based on Norman Fairclough's theory, which includes three levels of analysis: text, discursive practice and social praxis. Additional data was obtained from relevant books, news articles, and journal articles. The research found that the @aniesbubble X account succeeded in creating an authentic and attractive political persona for the younger generation through the use of glocalization and cultural hybridity strategies. The account also demonstrates the dynamic interaction between global and local influences, and is able to convert social capital into economic capital through the active participation of fans. The findings suggest that social media plays an important role in shaping political and cultural narratives.